Low Serum Methylglyoxal Levels Correlate with Psoriasis Severity and Inflammatory Response Indices - Aleksandra Damasiewicz-Bodzek; Agnieszka Nowak; Maciej Maciejczyk; Sławomir Waligóra; Brygida Przywara-Chowaniec (Pathophysiology)
Psoriasis is a multifactorial inflammatory disease. Methylglyoxal (MG) is a highly reactive dicarbonyl compound responsible for dicarbonyl stress in some inflammatory conditions, and it may play a role in the etiopathogenesis of psoriasis. Methods: A total of 50 patients with psoriasis and 35 healthy individuals participated in this study. The following indices were assessed in patients: Body Surface Area (BSA), Psoriasis Area and Severity Index (PASI), and Dermatology Life Quality Index (DLQI). MG concentration was evaluated in blood samples. The following inflammatory response indices were calculated: Systemic Inflammation Response Index (SIRI), Systemic Immuno-inflammation Index (SII), and Aggregate Index of Systemic Inflammation (AISI). Results: An analysis of the obtained data showed a statistically significant decrease in the mean serum MG concentration in patients with psoriasis when compared to the healthy individuals (1.19 ± 0.4 μg/mL vs. 1.75 ± 0.6 μg/mL; p = 0.000002). In the patients, MG concentration correlated negatively with psoriasis disease severity indicators (BSA and PASI), C-reactive protein (CRP) concentration, and inflammatory response indicators (SII and AISI). Conclusions: The decreased concentration of MG may be attributed to an increased accumulation of its derivatives (advanced glycation end-products) in the inflamed skin and/or scavenging by polyamines.